Webster's new world : - Wason, Sara D. (Wiley, 2004)
A superior resource to help your nonprofit win the grants you deserve. In an increasingly competitive nonprofit world, even top organizations struggle to extend their fundraising reach or simply maintain current funding levels. This thorough guide to crafting winning grant applications takes you through the entire process--from pinpointing the right funding opportunities, to writing persuasive proposals, to following up later. Practical, reliable, and accessible to seasoned pros and grant-writing greenhorns alike, Webster’s New World Grant Writing Handbook provides comprehensive coverage of: Different types of foundation and corporate grantmakers, Defining your project, as well as your organization’s mission and goals ...